ON THE QUESTION OF MASS-ENERGY CHARACTERISTICS OF VARIOUS AVIATION SOURCES OF ELECTRICITY - A. V. Kechin (Научный вестник МГТУ ГА, 2018)
The article raises the issue of the synthesis of power supply systems for new generation aircraft, which is understood as: the power supply system (complex) of the aircraft, which includes the power and information structures closely integrated. Using this method, the power generation, transformation and distribution functions are assigned to the power structure, and the information structure provides work algorithms. The problematic of the synthesis of the described systems is formed and its relevance is justified. The main work done abroad and on the territory of the Russian Federation aimed at solving this problem are analyzed. As a solution to the problem, it is proposed to use the actual, from the point of view of the authors, method – the structural-functional method. It is shown that the structural-functional method is applicable to solving complex engineering problems, as shown in the examples [16, 18]. The chosen method of solving this problem, like any other one, requires a sufficient number of bench-mark data. When applying the structural-functional method, which is data of the "constraint" type, i.e. GOST (All-Union State Standard) and OST (All-Union Standard) requirements, technical specifications, supplemented by data on possible elements of the synthesized scheme. This article is mainly devoted to the choice of parameters of possible elements of the synthesized circuit, namely primary electric power sources. The article defines a technique for converting discrete values of primary energy sources into functional dependencies, as well as restrictions imposed on their approximating functions. The example shows the obtaining of functional dependencies for mass-energy indicators of nickel-cadmium storage batteries produced by VARTA and SAFT. The analysis of the obtained results is shown, which showed their sufficient reliability and, as follows, their applicability in the development of aircraft power supply systems.